Wavelet Coherence Analysis of the Relationship Between Commodity Indices and Streaming Quotes for Futures for Gold, Zinc and Nickel - Haponenko, O.; Baranova, V.; Lyashenko, V. (International Journal of Academic Multidisciplinary Research, 2023)
Data analysis is one of the research tools. This process allows you to assess the current situation, to obtain additional information. This is especially important in the study of economic data, whe n we operate with the available information and it is necessary to make informed decisions. This paper discusses the features of the analysis of data on the stock market for such commodity as gold, zinc and nickel. The stock market is an important structural element in the formation of market relations. To study it, there are many different indicators and parameters. We highlight commodity indices and futures quotes. Their mutual analysis allows you to better understand the dynamics of the market, to reveal trends in its change. For these purposes, we use wavelet coherence estimates, which are presented in the form of diagrams. We provide a lot of graphs, which allows you to understand the course of the study and evaluate the results.
Keywords: commodity indices; wavelet coherence